Ground and norm of morality : ethics for college students - Reyes, Ramon Castillo (Quezon City, Philippines : Ateneo De Manila University Press, 1989)
This book is college textbook in general ethics. It is not meant only for those who are philosophy majors. Technical philosophical terms are not used, except those that a college student might be expected to know from one or two other basic college philosophy courses usually required of him.
1. Introduction: preliminary notions -- 2. Siddhartha Gautama -- 3. Confucius -- 4. Plato -- 5. Aristotle.
Includes index.
Keywords: ETHICS